2015
DOI: 10.5152/tjg.2014.7014
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine versus alfentanil combined with propofol for sedation in colonoscopy procedures: A randomized prospective study

Abstract: Background/Aims: Different drug combinations are used for sedation in colonoscopy procedures. A ketaminepropofol (ketofol) mixture provides effective sedation and has minimal adverse effects. Alfentanil also provides anesthesia for short surgical procedures by incremental injection as an adjunct. However, no study has investigated the use of ketofol compared with an opioid-propofol combination in colonoscopic procedures. Materials and Methods: A total of 70 patients, ASA physical status I-II, scheduled to unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 15 publications
0
10
1
1
Order By: Relevance
“…However, the discharge time in both groups was comparable. This was different from the study of Turk and colleagues [17] . Their study compared the ketofol with the combination of alfentanil and propofol in elective colonoscopic patients.…”
Section: Discussioncontrasting
confidence: 83%
“…However, the discharge time in both groups was comparable. This was different from the study of Turk and colleagues [17] . Their study compared the ketofol with the combination of alfentanil and propofol in elective colonoscopic patients.…”
Section: Discussioncontrasting
confidence: 83%
“…11,12 Based on anecdotal data, the use of adjunct sedatives or deep sedation is often used with these patients. [19][20][21][22][23] Because of its hypnotic and sedative properties, diphenhydramine is recommended for endoscopic procedures in difficult-to-sedate patients, but the studies supporting its use have yielded conflicting results. 13,18 We designed a randomized controlled study to systemically analyze the use of diphenhydramine as an adjunct to routinely used sedatives in patients on chronic opioids.…”
Section: Discussionmentioning
confidence: 99%
“…In studies performed by Türk et al 8 , propofol was combined with ketamine and alfentanil for sedation in colonoscopy procedures. Between the 2 protocols, it was observed that the combination of propofol and ketamine resulted in a longer time to onset of sedation and a longer duration of action.…”
Section: Discussionmentioning
confidence: 99%
“… 6 Ketamine has amnesic and analgesic properties and therefore is well-suited for short procedures. 7 , 8 This prospective, randomized, double-blind study planned to compare propofol/alfentanil and propofol/ketamine combinations for use during UGSEMOP.…”
mentioning
confidence: 99%